Multi-target Pharmacological Effects of Platycodin D - Zhang, Zhong-rong; Chan, Chun W. (Mini-Reviews in Organic Chemistry, 2017)
Plant secondary metabolites are considered as a valuable source to identify promising lead compounds for developing novel drugs. Platycodin D is regarded as one of the major bioactive compounds in medicinal plant Platycodon grandiflorum, which attracts researchers to study its therapeutic effect recently. This paper reviews the latest research of biological and pharmacological activities of platycodin D. In vitro and in vivo experimental evidences have revealed that platycodin D demonstrates multiple pharmacological properties including anti-oxidative, anti-inflammatory, anticancer, antiobesity and hepatoprotective effects. The underlying mechanisms of multiple therapeutic functions of platycodin D are very likely associated with its anti-inflammatory and antioxidant nature, whereas low bioavailability should be considered in drug development.
Keywords: anti-inflammation